Improving Students Independence And Learning Achievement In Mathematics Teaching Through Problem Based Instruction (PBI) On The Topic Of Circle (CAR of Mathematics Learning in Grade VIIIA of SMP Al Islam 1Surakarta Academic Year 2012/2013) - Anshori, Thoriq Saiful; , Rita P. Khotimah, S.Si., M.Sc (2013)
This research aims to know the improving of learning independence and student achievement in mathematics learning through Problem Based Instruction (PBI) on the topic of the circle. This research uses a qualitative approach by the design of Classroom Action Research (CAR), which is implemented in three cycles. Researcher and mathematics teacher of grade VIIIA SMP Al Islam 1 Surakarta as the subject of the action given. While students of grade VIIIA by the number 32 students is the subject receiving the action. Data collection method used are observation, field notes, tests, documentation. The data analyzed by descriptive qualitative use flow method which are data reduction, data presentation and data verification. Based on the research results, it can be concluded that the application of Problem Based Instruction (PBI) can increase independence learning and students achievement in mathematics learning of students at grade VIIIA. It can be seen from several indicators: 1) the student‟s courage in expressing opinions/questions increases from 22.59% to 70.00%, 2) the student‟s ability to solve the problems independently in a group increases from 32.26% to 76, 66%, 3) the student‟s ability to work in group by teamwork increases from 38.71% to 76.66%, 4) the student‟s confidence in solving individual problems increases from 48.39% to 83.33%, 5) the student‟s ability to achieve test scores based on KKM standardized increases from 38.71% to 86.67%.